A Capability Approach to Unemployed Young People's Voice and Agency in the Development and Implementation of Employment Activation Policies. (24th October 2016) - Egdell, Valerie; Graham, Helen
Abstract: In the UK, current approaches to employment activation are primarily concerned with rapid labour market entry, with jobseekers compelled to engage in activities or be sanctioned. The Capability Approach (CA) has been proposed as an alternative framework to measure successful employment activation. It is concerned with what people can do rather than what they actually do, together with their substantive freedom of choice. In applying the CA, attention is drawn to the need for jobseekers to have a voice in the design and implementation of employment activation programmes. Drawing on in‐depth qualitative research, this article uses the CA to explore the voice and agency of unemployed young people (aged 16–24) in the development and implementation of employment activation policies. It analyses how far, and in what ways, young people's ideas, experiences and voices are included in policy development and implementation. Reflections and conclusions are made about how the policy discourse which has stressed the importance of centring services on the needs of users is reflected in employment activation policy.